Mjölkkors behov av att ligga och att sova - Nilsson, Emma (2009)
The aim of this literature review was to investigate whether the modern dairy cow has the time she needs to lie down and to sleep and what deprivation of these behaviors could lead to. Current research seems to agree on the fact that sleep is essential but there is no uniform explanation of the function of sleep, even though there are many theories. It is known that sleep has an important impact on the immune system and that sleep is increased in case of an infection. Sleep deprivation causes many negative effects including reduced function off the immune defense, increased metabolic activity, malnutrition and increased heart rate. It has also been found that deprivation of sleep could cause increased mortality. In cows very few studies have focused on the need of sleep and time to lie down, and deprivation of these behaviors. Cows have a strong motivation to lie down and they sleep 4 hours a day according to the only study found on duration of sleep in cows. Time budget is an expression that tells how much time cows use for different behaviors, such as lying down, eating and ruminating. The cow’s time budget can be used as a welfare indicator on the farms and the time budget could be influenced by many things. There is no well-developed tool to predict whether cows under specific conditions get enough time to lie down and to sleep. This together with the fact that there is limited information about cows sleeping- and lying behavior makes it impossible to exclude that the cows are suffering of sleep- and lying deprivation. Based on this literature review it is suggested that mastitis and metabolic disorders, which are common in dairy cows, could have a connection to sleep deprivation. More research on this subject is needed.